“It seemed like she just wanted me to suffer”: Acts of obstetric racism and birthing rights violations against Black women - Dorian S. Odems; Erica Czaja; Saraswathi Vedam; Na’Tasha Evans; Barbara Saltzman; Karen A. Scott (SSM: Qualitative Research in Health)
Introduction: Studies that examine obstetric violence and mistreatment during perinatal care demonstrate that Black women experience higher levels of harm and abuse than other racialized groups. Yet these gender-based concepts do not fully recognize the intersectional gender-and race-based harms that Black women experience within the context of quality, safety, and human rights violations in the U.S. healthcare system. Methods: We performed qualitative secondary analysis from Black women participants in the Giving Voice to Mothers (GVtM) study (n = 304). Primary data collection for the GVtM survey spanned from 2016 to 2017, and our analysis occurred in 2023, focusing on the interpretation of open-ended responses to three categories of inquiry: worst experiences with perinatal care, experiences of being pressured to undergo medical interventions, and desired revisions to birthing experiences. We employed a deductive approach and applied two analytic frameworks – obstetric racism and the Black Birthing Bill of Rights (BBBR)– to categorize Black women's narratives of harm during perinatal care as quality, safety, and human rights violations. Results: Black women described perinatal care experiences with considerable violations of the BBBR, including disrupted time with babies, racially discordant care, and unaffordable care. These experiences illustrated all six domains of obstetric racism. Conclusion: This study contributes to an emerging body of Black feminist approaches to knowledge production in obstetric patient safety, emphasizing the critical intersection of gender and race. Furthermore, this study underscores the value of using Black-women-defined frameworks with typologies to interpret the distinct experiences of Black women instead of the more limited gender-based concepts of obstetric violence, mistreatment, and respectful maternity care that lack historical context and contemporary implications of anti-Black racism and misogynoir.